Penerapan Modifikasi Motif Kangkung Batik Tanah Unesa pada Outer Ready-To-Wear - Alfiyah Yaziidah Azizirrohmah; Irma Russanti (Universitas Negeri Surabaya, 2023)
The modification of the kangkung motif has a beautiful and bright color. The aim of the study was to apply modifications to the Unesa land kangkung motif on outer ready-to-wear designs and the finished product of applying modifications to Unesa soil kangkung motifs to outer ready-to-wear. This research method uses the Double Diamond approach. This method consists of 4 stages Discover, Define, Develop, and Deliver. At the discover stage, we collect insights about the modification of the kangkung motif and understand the outer ready-to-wear fashion trends. Define stage, looking for sources of ideas and ideas that will be used to produce outer ready-to-wear in the form of moodboards. The develop stage, the development of 10 designs according to the moodboard. Followed by the deliver stage, design selection and manufacture of outer ready-to-wear products. Then data was collected by 6 lecturers of fashion design and D4 Fashion Design students who had taken batik and casual wear/clothing production courses. Data collection was analyzed using descriptive quantitative by looking for the mean (average) which showed that based on 10 developments of outer ready-to-wear designs, the observer chose design 8 with a total average of 4.71 out of 5 aspects belonging to the very good category and the results so outer ready-to-wear as a design embodiment has a total average of 4.15 belonging to the good category so that it can be stated that the finished outer ready-to-wear can be well received. Keywords: Modification of the kangkung motif, Unesa soil batik, outer, ready-to-wear